An Example of Task Oriented Empirical Evaluations of 3D-Display Modes - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Journal of Universal Computer Science)

Visualization of meteorological data using an interactive flight - Koenig, M; Lenz, Christian; Domik, Gitta (Proceedings. Computer Graphics International (Cat. No. 98EX149))

Fuzzy dynamics of compartmental systems - Hüllermeier, Eyke (in Proceedings EUFIT-98 6th European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Efficient Consistency Checking for Embedded Memories - N. Yarmolik, Vyacheslav; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Efficient Consistency Checking for Embedded Memories - N. Yarmolik, Vyacheslav; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

A Distributed Computer Architecture for Fast Qualitative Simulation - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold

An optimal checkpointing interval for real-time systems - Karl, Holger; Werner, Matthias (Proc. Intl. Conf. Parallel and Distributed Processing Techniques and Applications)

Snarks and reducibility - Brinkmann, Gunnar; Steffen, Eckhard (Ars Combinatoria)

Chromatic-index-critical graphs of Orders 11 and 12 - Brinkmann, Gunnar; Steffen, Eckhard (European J. Combinatorics)

Classification and characterizations of snarkse - Steffen, Eckhard (Discrete Mathematics)

Acceleration of satisfiability algorithms by reconfigurable hardware - Platzner, Marco; De Micheli, Giovanni (Proceedings of the 8th International Workshop on Field Programmable Logic and Applications (FPL))

Reflectance Anisotropy of GaAs(100): Theory and Experiment - Shkrebtii, A. I.; Esser, N.; Richter, W.; Schmidt, Wolf Gero; Bechstedt, F.; Fimland, B. O.; Kley, A.; Del Sole, R. (Physical Review Letters)

Geometry and electronic structure of InP(001)(2×4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

Atomic structure of InP(001)-(2×4): A dimer reconstruction - Schmidt, Wolf Gero; Bechstedt, F.; Esser, N.; Pristovsek, M.; Schultz, Ch.; Richter, W. (Physical Review B)

In-induced (4 × 2) reconstructions of GaAs(001) surfaces - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Applied Surface Science)

Ultrasonic sensors for process monitoring and chemical analysis state of the art and trends - Hauptmann, Peter; Lucklum, Ralf; Püttmer, Alf; Henning, Bernd (Sensors and Actuators A: Physical)

Zum Partikeltransport in Elektrischen Abscheidern - Schmid, Hans-Joachim

Knowledge based controller selection for electrical drives with imperfect mechanic - Schutte, F.; Beineke, S.; Grotstollen, H. (IECON '98. Proceedings of the 24th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.98CH36200))

Modellierungund Regelung stromrichtergespeister Ultraschall-Wanderwellenmotoren - Maas, J.

Axiomatische Ethik - Peckhaus, Volker (Zwischen Kant und Hare. Eine Evaluation der Ethik Leonard Nelsons)
Autoreferat: Zbl. Math. 914.00010.